2002
DOI: 10.3727/096020198389834
|View full text |Cite
|
Sign up to set email alerts
|

Islet Transplantation under the Kidney Capsule Corrects the Defects in Glycogen Metabolism in Both Liver and Muscle of Streptozocin-Diabetic Rats

Abstract: Insulin-deficient rats are characterized by multiple defects in the pathway of glycogen synthesis and breakdown in both liver and skeletal muscle. The aim of this study was to clarify whether islet transplantation under the kidney capsule, which is associated with delivery of insulin into the peripheral circulation, is able to normalize glycogen metabolism in liver and muscle of streptozotocin-diabetic rats. Three groups of male Lewis rats were studied under fasting condition: controls, untreated diabetics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…It is the only site in humans associated with achieving insulin independence [7]. Other sites have been used, such as the renal capsule [54][55][56][57], spleen [53,58], omentum [59], and peritoneal cavity [60,61], but have rarely been associated with function of islet autografts in humans [62,63]. Presumably, islets survive by nutrient diffusion and have reduced functional capacity until neovascularization occurs [64,65].…”
Section: Infusion Considerationsmentioning
confidence: 99%
“…It is the only site in humans associated with achieving insulin independence [7]. Other sites have been used, such as the renal capsule [54][55][56][57], spleen [53,58], omentum [59], and peritoneal cavity [60,61], but have rarely been associated with function of islet autografts in humans [62,63]. Presumably, islets survive by nutrient diffusion and have reduced functional capacity until neovascularization occurs [64,65].…”
Section: Infusion Considerationsmentioning
confidence: 99%
“…In this study, we have shown that islets seeded into vascularized chambers reduce hyperglycemia in STZ‐induced diabetic mice just as effectively as islets injected under the renal capsule, the “benchmark” procedure (6).…”
Section: Discussionmentioning
confidence: 91%
“…Anatomic Sites for Islet Cell Transplantation Different anatomic locations were tried for the engrafting of the islet cells. [35][36][37] The liver is currently the preferred target organ for islet cell transplantation in humans. The portal vein is the preferred site of infusion, 36 given the relative ease of access and the high venous flow with a double circulation system (arterial and portal venous) of the liver, allowing engraftment more likely without infarction.…”
Section: The Islet Cell Transplant Proceduresmentioning
confidence: 99%
“…The kidneys are used as a site of infusion for islet cells primarily in animal experimental islet cell transplantation. 35 Islets are injected under the kidney capsule, a well-vascularized area of the organ. This site is a less attractive one in humans because the kidney is less accessible for surgery or interventional radiology.…”
Section: The Islet Cell Transplant Proceduresmentioning
confidence: 99%